Modulation of the Electrocatalytic Activity of Fe Phthalocyanine to Carbon Nanotubes: Electrochemistry of L-Cysteine and L-Cystine - Zagal-Moya, J; Zagal-Moya, J; Silva-Rojas, J; Silva-Rojas, J; Silva-Gonzalez, N; Silva-Gonzalez, N; Oyarzun-Medina, M; Oyarzun-Medina, M; Ramírez-Pastén, S; Ramírez-Pastén, S; Gutierrez-Ceron, C; Gutierrez-Ceron, C (Elsevier Ltd, 2019)
We have evaluated the electrocatalytic activity of hybrid electrodes containing Fe(II) phthalocyanine and tested these electrodes for L-cysteine oxidation and L-cystine reduction. The hybrid electrodes consisted of pristine multi-walled carbon nanotubes and functionalized with [sbnd]COOH, [sbnd]NH2 groups (MWCNT-p, MWCNT-c and MWCNT-a). These MWCNTs were modified with iron (II) phthalocyanine (FePc). The characterization of the hybrid systems was performed using X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and AFM with the purpose of elucidating the type of interaction between FePc and MWCNTs. The Fe(II)/(I) and Fe(III)/(II) redox potentials associated with the metal center where evaluated using cycling voltammetry. The redox processes are slightly affected by the presence of MWCNTs. The activity for both reactions increases substantially by the presence of modified MWCNTs essentially by an area effect. However, when the currents are normalized by the amount of active sites estimated from the surface coverages of FePc, the activities are still higher for FePc attached to MWCNTs. The data for L-cysteine oxidation fits well on a volcano correlation published previously for several metal phthalocyanines and metalporphyrins. © 2019